2019
DOI: 10.2147/ijgm.s218799
|View full text |Cite
|
Sign up to set email alerts
|

<p>The serum concentration of vitamin B<sub>12</sub> as a biomarker of therapeutic response in tuberculosis patients with and without human immunodeficiency virus (HIV) infection</p>

Abstract: BackgroundPrior to clinical trials of new tuberculosis (TB) drugs or therapeutic vaccines, it is necessary to develop monitoring tools to predict treatment outcomes in TB patients.MethodsMicronutrients concentration level was determined from a total of 262 study participants with five clinical groups: 57 TB patients coinfected with HIV (HIV+TB+), 87 active TB Patients (TB cases), 71 HIV infected without active and latent TB infection (HIV+TST-), 22 latent TB infection (TST+) and 25 healthy controls (TST-). Vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This enzyme is involved in Vitamin B12 synthesis, and degradation of amino acids, short-chain fatty acids and cholesterol [72]. Thus, the abundance of this enzyme and MTB's capacity for de novo biosynthesis of vitamin B12 [73], resulting in reports of elevated B12 vitamin in TB patients [74], could account for our observation. The abundance of methylmalonyl-CoA mutase in only TB-DM group is intriguing and could be the body's homeostasis activity [75].…”
Section: Discussionmentioning
confidence: 55%
“…This enzyme is involved in Vitamin B12 synthesis, and degradation of amino acids, short-chain fatty acids and cholesterol [72]. Thus, the abundance of this enzyme and MTB's capacity for de novo biosynthesis of vitamin B12 [73], resulting in reports of elevated B12 vitamin in TB patients [74], could account for our observation. The abundance of methylmalonyl-CoA mutase in only TB-DM group is intriguing and could be the body's homeostasis activity [75].…”
Section: Discussionmentioning
confidence: 55%
“…Vitamin B12 concentration in the blood could be a biomarker in the identification of active tuberculosis with and without HIV infection, according to a recent study. Detecting the concentration level of these micronutrients in HIV-uninfected patients could be used as a TB treatment response monitoring biomarker [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cobN gene encodes a critical protein for the synthesis of vitamin B12, which is essential for MTB proliferation and disease progression (Savvi et al, 2008). Gebremicael et al (Gebremicael et al, 2019) suggested that the serum concentration of vitamin B12 might be used as a diagnostic biomarker for active TB. Some of the mutations associated with poor outcomes were found in genes of unknown function, such as Rv2164c, Rv0648 and Rv3148 , but if their association with treatment outcomes is confirmed in subsequent studies, they might be worth further investigation (Figure 2−figure supplement 2).…”
Section: Discussionmentioning
confidence: 99%